Time‐Varying Fund Manager Skill - KACPERCZYK, MARCIN; NIEUWERBURGH, STIJN VAN; VELDKAMP, LAURA (Journal of Finance, 2014)
ABSTRACT We propose a new definition of skill as general cognitive ability to pick stocks or time the market. We find evidence for stock picking in booms and market timing in recessions. Moreover, the same fund managers that pick stocks well in expansions also time the market well in recessions. These fund managers significantly outperform other funds and passive benchmarks. Our results suggest a new measure of managerial ability that weighs a fund's market timing more in recessions and stock picking more in booms. The measure displays more persistence than either market timing or stock picking alone and predicts fund performance.